P024 Genetic determinants of antifungal drug resistance in Fusarium solani species complex. (20th September 2022) - Trivedi, Pinal; Gajjar, Devarshi
Abstract: Poster session 1, September 21, 2022, 12:30 PM - 1:30 PM: Due to its challenging diagnosis and treatment, fungal keratitis is one of the most serious kinds of corneal infection. The Fusarium solani species complex is responsible for nearly half of all fungal keratitis cases. Fusarium infection is difficult to treat because of the increased antifungal resistance of Fusarium species. Objective: To check the antifungal susceptibility in keratitis-causing isolates of F. solani species complex. To find the genetic determinants of resistance using whole genome sequencing. Methodology: Prior to AFST and according to CLSI, clinical isolates of Fusarium species ( n  = 5) were cultured on potato dextrose agar for 7 days at room temperature. Fungal spores were harvested using 0.8% NaCl and antifungal drug susceptibility testing of 6 different antifungal drugs were tested using CLSI standards broth microdilution method and minimum inhibitory concentrations were obtained. After 24 and 48 h, broth microdilution plates were manually examined. The wells for growth control were also examined. The minimum inhibitory concentration of anti-fungal drugs was the lowest dose that inhibits growth completely (compared to the growth control well). Minimal effective concentration (MEC) was also determined against antifungal drugs. Whole genome sequencing was done using Illumina Hiseqx10. Bioinformatics analysis was done using different bioinformatics tools and software (FASTQC, SPAdes, OmicsBox, AUGUSTUS, etc.). Results: In this study the antifungal drug susceptibility from average MIC value were found as fluconazole (512  μ g/ml) > itraconazole (32  μ g/ml) > amphotericin B (8  μ g/ml) > natamycin (8  μ g/ml) > posaconazole (2  μ g/ml) > voriconazole (1  μ g/ml). Fluconazole had a higher MIC value (512 g/ml) in all isolates, however, voriconazole was shown to be more sensitive, with a lower MIC range (0.25-4 g/ml). Glyoxalase/Bleomycin resistance protein, mfs—multidrug resistance transporter, fusaric acid resistance protein, efflux pump antibiotic resistance protein, and copper resistance protein were found by genome-based analysis. Conclusion: As a conclusion of this study, we observed antifungal drug resistance in Fusarium spp., which is often used to treat keratitis in patients, employing fluconazole, itraconazole, and amphotericin B. Resistance to first-line azoles was as a gene variant which contributed to antifungal drug resistance. This study using the phenotypic and genotypic characterization of drug resistance patterns will help to combat antifungal drug resistance.